MODIFIKASI PEMAHAMAN 5 PILAR DIABETES MELITUS PADA PASIEN DAN KELUARGA DALAM UPAYA PENCEGAHAN HIPERGLIKEMIA DAN HIPOGLIKEMIA - Eriyani, Theresia; Shalahuddin, Iwan (Universitas Mataram, 2025)
to impaired insulin production or use in the body. One of the key approaches to managing diabetes is health education. Objective, Health education about DM plays an important role in increasing public understanding of risk factors, prevention, and proper management of diabetes. Method, Health education carried out by the author is at Al-Ihsan Hospital Umar bin Khattab room on the 3rd floor with most patients with DM disease. Therefore, the health education carried out is themed on knowledge about Diabetes Mellitus and its treatment through the 5 pillars of DM. The results of the activity, learning outcomes or knowledge improvement as an indicator of the achievement of health education are seen from changes in test scores by participants before and after the presentation. In conclusion, the results were obtained that there was an increase in test scores before and after the presentation was carried out and there was an activeness of participants during the presentation through question and answer sessions and discussions. Recommendation, It is hoped that the health education carried out can be useful for the community in increasing knowledge and can be applied in daily life so that DM can be controlled and the incidence rate decreases. In addition, it is hoped that participants can also share their knowledge with their families or other close people.